Measuring Dependence Severity Of Ketum (Mitragyna Speciosa) Use Among Ketum Leaf Users In Malysia - Singh, Darshan Singh Mahinder (2013)
Ketum or M.speciosa is an indigenous psychotropic plant commonly used for its medicinal value. Studies on ketum use is still scarce, hence further research is needed to elucidate its prolonged use risk in humans. Study aim to determine the sociodemographic characteristics, measure ketum dependence severity, ketum withdrawal severity, ketum craving intensity and analyze the social functioning of ketum leaf users. A total of 293 ketum users were surveyed from three northern states of peninsular Malaysia (Penang, Kedah and Perlis). A cross-sectional study design using non-probability sampling techniques (purposive and quota) was used to collect data. Four study instruments specifically the Leeds Dependence Questionnaire, Marijuana Withdrawal Checklist, Marijuana Craving Questionnaire- Short Form, and Addiction Severity Index were used to measure ketum dependence severity among ketum leaf users. Respondents were all male, majority of Malay ethnicity. Eighty-five percent were employed, 46% were between the ages of 18-25 years, 41% were married, while three-fifths had completed eleven years (SPM) of education. Seventy-nine percent reported that they need to use ketum daily, 83% reported ketum can cause addiction if used regularly, 64% encountered sleeping problems, 67% became nervous, 72% were unable to control ketum desire and 90% had better social-functioning.